2015
DOI: 10.18331/brj2015.2.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous saccharification and fermentation of cassava waste for ethanol production

Abstract: Please cite this article as: Pothiraj C., Arun A., Eyini M. Simultaneous saccharification and fermentation of cassava waste for ethanol production. The efficiency of enzymatic and microbial saccharification of cassava waste for ethanol production was investigated and the effective parameters were optimized. The mixture of amylase and amyloglucosidase (AMG) resulted in a significantly higher rate of saccharification (79.6%) than the amylase alone (68.7%). Simultaneous saccharification and fermentation (SSF) yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 19 publications
(21 reference statements)
0
13
0
1
Order By: Relevance
“…Coupling COSLIF with separate hydrolysis and fermentation (SHF) is supposed to enhance ethanol yields. Higher ethanol yields with lower potential costs have typically been reported from simultaneous saccharification and fermentation (SSF); however, a few studies showed that SHF yields a more than 20% improvement in ethanol production over SSF at very high solids concentrations by using newly preparations of a cellulolytic enzyme, Cellic ® CTec 2 …”
Section: Introductionmentioning
confidence: 99%
“…Coupling COSLIF with separate hydrolysis and fermentation (SHF) is supposed to enhance ethanol yields. Higher ethanol yields with lower potential costs have typically been reported from simultaneous saccharification and fermentation (SSF); however, a few studies showed that SHF yields a more than 20% improvement in ethanol production over SSF at very high solids concentrations by using newly preparations of a cellulolytic enzyme, Cellic ® CTec 2 …”
Section: Introductionmentioning
confidence: 99%
“…Os autores sugeriram que a biomassa residual do caule de M. esculenta pudesse ser usada como matéria-prima sustentável para a produção de etanol. Pothiraj et al (2015) avaliaram a eficiência da liquefação microbiana e enzimática, e sacarificação de resíduos de mandioca para a produção econômica de etanol utilizando Zymomonas mobilis. Os resultados deste estudo indicaram que a sacarificação microbiana e fermentação de resíduos de mandioca envolvendo Z. mobilis podem ser usados para melhorar a produção de etanol a partir de resíduos de mandioca ou outros resíduos de amido para reduzir o custo de produção de etanol, reduzindo o tempo total do processo completo.…”
Section: Resultsunclassified
“…Therefore, biofuels such as biogasoline, both as it is and as a mixture, are needed for a sustainable transportation system. Biogasoline itself is an alternative energy produced from plants such as corn, sugar cane, and cassava [6]- [9]. Biogasoline from biomass is able to produce lower exhaust emissions compared to gasoline [10].…”
Section: Introductionmentioning
confidence: 99%